UJI AKTIVITAS EKSTRAK ETANOL DAUN SIRIH CINA (PEPEROMIA PELLUCIDA L.) TERHADAP BAKTERI PSEUDOMONAS AERUGINOSA DAN PROPIONIBACTERIUM ACNES - Helsi Herdiani Sinaga; Astriani Natalia br Ginting; Nerly Juli Pranita Simanjuntak (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2026)
The Chinese betel leaf plant (Peperomia pellucida L.), a herbal plant belonging to the Piperaceae family, has antibiotic properties against the growth of acne-causing bacteria. The Chinese betel leaf plant is also known to have antibacterial activity. This study aimed to determine the antibacterial activity of the ethanol extract of Chinese betel leaf against Pseudomonas aeruginosa and Propionibacterium acnes. The method used was disc diffusion with varying concentrations of 10%, 20%, and 30%. Inhibition zone data were analyzed using a One-Way ANOVA test. The results showed that the ethanol extract of Chinese betel leaf was able to inhibit the growth of both bacteria and there was a significant difference between extract concentrations (p < 0.05). The ethanol extract of Chinese betel leaf has the potential as a natural antibacterial.